Acute Pancreatitis in a Patient with Vivax Malaria - Sharma, Vishal; Sharma, Alka; Aggarwal, Amitesh; Bhardwaj, Gaurav; Aggarwal, Sourabh (JOP. Journal of the Pancreas, 2012)
Context Acute pancreatitis is most commonly linked to gallstone disease or alcohol consumption. Occasionally it can follow infectious disease. Malaria, especially Plasmodium falciparum infection, has been associated with acute pancreatitis. Case report We present the case of a 17-year-old male who presented with a history of fever, abdominal pain and hypotension and revealing acute pancreatitis associated with infection by Plasmodium vivax. Conclusion Acute pancreatitis can accompany malaria, including Plasmodium vivax.